INCREASING THE ENERGY EFFICIENCY OF ELECTRIC DRIVES OF SUBWAY CARS - Kulbashna, N.; Daleka, V.; Kulbashnyi О. (Municipal economy of cities. Series: «Economy science», 2023)
The article proposes the use of a frequency-controlled drive for regulating asynchronous electric motors used on subway cars. The proposed solution creates all the grounds for increasing the energy efficiency of electric cars and, in general, the entire metro. Taking into account that the subway is one of the most used types of urban transport in large cities of Ukraine and at the same time consumes a significant part of electricity, therefore, in the conditions of rising prices for energy resources, these issues become the most urgent. It is shown that the methods of regulation of subway engines are not covered widely enough in scientific research, but the methods of increasing the energy efficiency of drives generally accepted in industrial spheres are a developed direction. This reveals the possibilities of integrating the developed methods for application on subway cars. The use of a frequency converter, which changes the frequency of rotation of the motor rotor by changing the frequency and amplitude of the supply voltage using vector and scalar control, is a generally accepted method of motor regulation. There are a number of conflicting findings in research regarding the use of scalar or vector control, with some favoring the induction vector control system. However, a clear regulation is not required to regulate the operation of metro engines. Therefore, the article considers scalar control, which has not lost its importance due to the ease of implementation and adjustment and is used in various areas of industry and transport. The parameters of the STDa 280-4B-UK type STDa 280-4B-UK traction asynchronous traction motor with a capacity of 180 kW, manufactured by the EMIT Cantoni Motors company, which are installed on subway cars of the 81-7036/7037 series, were used for the study. The parameters of the T-substitution scheme of the asynchronous electric drive and the numerical values ​​of the vectors of the asynchronous motor were calculated. To analyze the operation of an asynchronous motor, the article uses the mechanical characteristic of the dependence of the motor torque on slippage at certain frequency values. It has been established that an asynchronous motor can operate stably only in a limited slip range, when the moment reaches its maximum value and the motor stops, as it has a load limit. The main reason for this is the increase in the influence of the active resistance of the stator winding when the supply voltage frequency decreases. The solution to this problem is the introduction of IR-compensation into the control system of the electric drive, which provides positive feedback on the stator current acting in the voltage channel. To demonstrate the effect of IR compensation, a comparison of mechanical characteristics was made before and after its introduction into the control system. Therefore, it was proved that the application of IR compensation is a promising direction of work, as the value of the electromagnetic moment increases significantly in the case of a low control frequency.